Choral, Public and Private Listener Responses to Hildegard Westerkamp's École - McCartney, Andra; McCarthy, Marta (Music and Arts in Action, 2012)
Hildegard Westerkamp's (1990) composition École Polytechnique is an artistic response to one of Canada's most profoundly disturbing mass murders, the 1989 slaying of fourteen women in Montreal, Quebec. Using the theoretical model, derived from Haraway, of the cyborg body, and analyzing the import of the mixed media (voices, instruments and electroacoustic tape) incorporated in the music, the authors examine the impact this work has had on some of those who have heard it and performed it, based on the responses of choristers and listeners in several studies. The authors explored how those who engaged significantly with the music, (including those who had no personal association with the actual events of the 1989 massacre), were able to make relevant connections between their own experience and the composition itself, embrace these connections and their disturbing resonances, and thereby experience meaningful emotional growth.
Accepted: 2012-11-14T10:25:30Z Publisher: University of Exeter

Musical Robots and the Serbian Kolo: A Narrative Analysis of Ana Sokolović’s Géométrie sentimentale (1997) - Harman, Brian (Circuit, 2012)
Composer Ana Sokolović divided her instrumental work Géométrie sentimentale into large sections inspired by pure geometric shapes — Triangle, Cercle and Carré — describing these sections as three contrasting perspectives of the same musical materials. This article uses a narrative analytical approach as a lens through which to understand these distinct sections and the materials populating them. Inspired by Sokolović’s employment of musical objects in her compositions and by the extra-musical concepts inspiring many of her works, this analysis uses a collection of colourful robot toys as metaphors for the work’s materials. Three unique perspectives of these toys are described: in Triangle, the robots interact as characters on a dramatic stage; in Cercle, they peacefully coexist in slow motion; and in Carré new combinations of robot elements are abruptly juxtaposed against each other. The characteristics and interactions between these toys, as well as the various harmonic ‘masks’ that the composer has them wear, are helpful in understanding Sokolović’s harmonic structure, variation/transformation techniques, formal organization and rhythmic characteristics. The Serbian kolo is also shown as influential on the work, relating directly to the physicality and kinetics of the metaphorical robots.
Publisher: Les Presses de l’Université de Montréal

The Vocal Music of Ana Sokolović: Love Songs for the Twenty-First Century - Bernstein, Tamara (Circuit, 2012)
Enchanted by the vocal music of Serbian-born Canadian composer Ana Sokolović, Tamara Bernstein visited the composer at her home in Montreal. Sokolović’s music draws on several sources, including the theatrical world and the culture of the Balkans. The extended vocal techniques in Sokolović’s music are rooted not in the avant-garde music of the twentieth century, but in the oral traditions and poetic voice of Serbia. It seems that the more the composer returns to her cultural roots, the more she embraces the universality of the human soul.
Publisher: Les Presses de l’Université de Montréal